COMMON AND SPECIFIC: HYBRID “LARGA / IVANIJA” TYPE AXES - POPA, Cristian Ioan (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The Larga-Ivanija type axes stand out both by their very small number and by their beauty. Summing up specific elements, found individually and in the case of other axes (semi-calotte flat, curved blade, decoration on the sleeve and so on), the use of the term hybrid axes is justified. Their similarity with Drajna-type axes is obvious, supporting their symbolic value. Their dating is relative, with no specific context, but they can be dated in the Late Bronze. The study aims to present morphologically each component of these axes, grouped by blade, handles, necks, ornaments. This detailed analysis allows both highlight both the common and the particular elements. Our approach is an extension of the study published in 2023. Scientific novelty. After the stage of outlining the main challenges offered by a hybrid type, we considered it essential to analyze some aspects in detail. Such ‘refinement’ allows us not only to observe the finest morphological details, but also how the latter are distributed geographically. Conclusions. Thus, taking into account the importance of the discoveries in Ukraine, we proposed in this study to use the compound term “Larga-Ivanija-type axes” instead of the term “Larga-type” used today by specialists in Romania and Hungary. There are two metallurgical areas that produced and used such very rare axes: western Ukraine, Transylvania and Maramureș. Their kinship with Drajna-type axes connects these regions to the widespread and dynamic trade of Bronze Age elites in the Balkan and Aegean area. Keywords: Larga-Ivanija type axes, prestige goods, Late Bronze Age, Carpathian Bronze Age metallurgy.